Upaya Guru dalam Menerapkan Pembelajaran Pendidikan Agama Islam Kurikulum Merdeka Siswa Kelas IV SDN 009 Bontang Utara - Mariana, Mariana; Syamsiar, Syamsiar (Sekolah Tinggi Ilmu Tarbiyah Syamsul Ma'arif Bontang, 2025)
Education plays a crucial role in developing human resources. A teacher must possess high abilities and qualities in guiding, educating, and teaching students. This study is a field research. Data was collected through interviews, observations, document analysis, and triangulation involving the Headmaster of SDN 009 Bontang Utara, the Curriculum Vice Principal, the Islamic Education Teacher, and fourth-grade students. The research findings indicate that the Islamic Education Teacher has successfully implemented the Merdeka Curriculum effectively. They provide academic education that aligns with the taught materials and educate students in courteous behavior. The learning process is also aligned with practices such as ablution, prayer, and memorization. However, even though students are granted freedom in the learning process, the teacher's understanding of the Merdeka Curriculum remains limited. Nevertheless, the performance of the Islamic Education Teacher at SDN 009 Bontang Utara continues to support the improvement of students' learning achievements. In conclusion, the Merdeka Curriculum provides opportunities for students to learn with freedom, yet further efforts are required to strengthen teachers' understanding of this curriculum. Thus, education in the school can continue to evolve and enhance the quality of human resources in the future.